EMPOWERMENT OF SMES THROUGH ACCESS TO SHARIA BANKING FINANCING FOR LOCAL ECONOMIC IMPROVEMENT - Permanasari, Lukita; Muhlis, Muhlis; Khunaifih, Robbah; Aini, Nur (Fakultas Ekonomi dan Bisnis Islam Universitas Al- Hikmah Indonesia - Jurnal Ekonomi Pengabdian Masyarakat, 2024)
Small and Medium Enterprises (SMEs) play a crucial role in driving local economic growth. However, one of the significant challenges faced by SMEs is limited access to financing, especially from conventional banking institutions. This study aims to explore the empowerment of SMEs through Sharia banking financing, which offers a more inclusive and ethical alternative in line with Islamic economic principles. The research utilizes a mixed-method approach, combining qualitative interviews with SME owners and quantitative data analysis from Sharia banking institutions to assess the extent of access and its impact on local economic improvement. The qualitative aspect focuses on understanding the obstacles and opportunities experienced by SMEs in securing financing, while the quantitative data provides an overview of the effectiveness of Sharia banking in supporting SMEs. The findings indicate that SMEs empowered through Sharia financing have shown increased financial stability, business expansion, and contributions to local economic development. However, challenges such as limited awareness and understanding of Sharia banking products remain significant. This study concludes that enhancing financial literacy and collaboration between SMEs and Sharia banking institutions is essential for maximizing the potential of Sharia-compliant financing in boosting local economies.